Estimation of the surface potential of clay mineral taking Na+/K+-specific ion effects into account - Gao, Xiaodan; Zhu, Zhihong; Zhang, Jin; Wang, Jingkuan; Xu, Yingde (Frontiers in Materials, 2022)
Surface potential is a key electrochemical property of colloid in the study of particle interactions. However, the specific ion effects is not involved in the existing measuring methods. In this study, approaches to the estimation of the surface potential of montmorillonite with or without consideration of the specific ion effects were explored through the montmorillonite particles aggregation in the presence of Li+, Na+, and K+. The montmorillonite aggregation process exhibited remarkable specific ion effects and the critical coagulation concentration (CCC) values show: Li+ (271.8 mM) > Na+ (130.8 mM)> K+ (85.04 mM). Based on the mathematic relationship between electrostatic repulsive and van der Waals attractive interaction at the CCC, the fluctuation coefficient β was obtained. The value of β could quantified the strength of the specific ion effects of different cations. Then the fluctuation coefficient β was introduced into the classical method for calculating the surface potential considering the specific ion effects. The quantificational sequence of ionic specificity of K+ and Na+ was: βK=1.433 > βNa =1.187. Simultaneously, the surface potential considering specific ion effects can be obtained by introducing this coefficient. Our findings provide ideas for getting reliable surface potentials of charged particles in different electrolyte environments.